A Conceptual Framework for Implementing Biosafety: Linking Policy, Capacity and Regulation - McLean, Morven A.; Frederick, Robert J.; Traynor, Patricia L.; Cohen, Joel I.; Komen, John (International Service for National Agricultural Research, 2002)
Given the challenges and difficulties inherent in building biosafety regulatory systems and needed capacity, the International Service for National Agricultural Research (ISNAR) convened an expert consultation in July 2001. The purpose of this meeting was to develop a conceptual framework to address biosafety regulatory implementation and capacity-building needs of developing countries. A five-element framework for national biosafety system implementation emerged, as described in this Briefing Paper. The conceptual framework clarifies critical decision points in the development or improvement of a national biosafety system, systematically examines choices among policy options and delineates some of the scientific and social dimensions of these options. It aims to complement ongoing regional and global projects that facilitate the development of national biosafety guidelines and frameworks.